Manajemen Perguruan Tinggi Swasta (Studi Kasus di Universitas Tjut Njak Dhien Medan) - Muhammad Akhir (Journal on Education, 2023)
The purpose of this study was to analyze the management of tertiary institutions at Tjut Njak Dhien University in Medan, both planning, implementation and evaluation. Kirk and Miller's qualitative research methodology. Observation data collection techniques, interviews and document studies. The findings of the study are the planning of the Medan UTND tertiary institution by establishing long-term development plans (RPJP), medium-term development plans (RPJM), annual work plans and budgets (RKAT) / operational plans (RENOP), development plans are arranged in a master development plan (RIP). ) and strategic master plan (RENSTRA). The implementation of the Medan UTND tertiary institution is embodied in the tri dharma of higher education, namely: education and teaching, training and development, community service. Leadership is democratic with the principle of deliberation. The evaluation of the Medan UTND tertiary institution was carried out based on eight main performance indicators (IKU), namely graduates, industry experience, academic lecturers, practicing lecturers, research results and community service, collaboration, project-based collaboration and case studies, standardized study programs.